DETERMINATION OF POROSITY AND GAS SATURATION FACTOR OF RESERVOIRS IN ACCORDANCE WITH PT-CONDITIONS OF OCCURRENCE - Bondarenko, M.; Kulyk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The porosity of the gas reservoir can be determined using a complex of radioactivity logging (RL) as the weighted arithmetic average of the apparent porosities from density log (DL) and neutron-neutron log (NNL). It is shown that the weight factors of averaging depend on the thermobarometric conditions of beds occurrence (primarily from the formation pressure). Weight factors depend on the density and the hydrogen index of gas, and also depend on lithologycal properties. A method for determination of gas saturation factor is proposed. Gas saturation factor is proportional to the ratio of the difference between apparent porosities of DL and NNL to the true porosity of the RL, with proportionality factor calculated similarly to weight factors of averaging. The parameters under investigation were estimated depending on the temperature and pressure conditions of beds occurrence to a depth of 8 km. Examples of the effect of abnormally high formation pressures for gas deposits of the Dnieper-Donets Depression are given. The effectiveness and informativeness of the developed approaches are demonstrated on an example of methanecoal cased well (Donets basin). Formation lithology is estimated, gas-saturated reservoirs are resolved, true porosity and gas saturation factor of reservoirs are determined.
Keywords: gas reservoir; complex of neutron logging and density logging; porosity and weight factors of averaging; gas saturation factor and proportionality factor; thermobarometric conditions